2009
DOI: 10.1124/jpet.109.160382
|View full text |Cite
|
Sign up to set email alerts
|

Glyceollin I, a Novel Antiestrogenic Phytoalexin Isolated from Activated Soy

Abstract: Glyceollins, a group of novel phytoalexins isolated from activated soy, have recently been demonstrated to be novel antiestrogens that bind to the estrogen receptor (ER) and inhibit estrogen-induced tumor progression. Our previous publications have focused specifically on inhibition of tumor formation and growth by the glyceollin mixture, which contains three glyceollin isomers (I, II, and III). Here, we show the glyceollin mixture is also effective as a potential antiestrogenic, therapeutic agent that prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 29 publications
4
92
0
Order By: Relevance
“…Then, these three components were purified and investigated separately: the active component of this mixture resulted to be glyceollin I, with an IC 50 value of 1.68 µM against ERα, whereas the IC 50 values of glyceollins II and III were 6.57 and >10 µM, respectively. Thus, this study demonstrated that glyceollin I acts as a potent ERs antagonist (Zimmerman et al, 2006). Moreover, further studies attributed the antiestrogenic activity of glyceollin I to the natural (−)-glyceollin I enantiomer, which was compared to those of the racemate and of the unnatural (+) enantiomer (Payton-Stewart et al, 2010).…”
Section: Natural Xenoestrogensmentioning
confidence: 67%
“…Then, these three components were purified and investigated separately: the active component of this mixture resulted to be glyceollin I, with an IC 50 value of 1.68 µM against ERα, whereas the IC 50 values of glyceollins II and III were 6.57 and >10 µM, respectively. Thus, this study demonstrated that glyceollin I acts as a potent ERs antagonist (Zimmerman et al, 2006). Moreover, further studies attributed the antiestrogenic activity of glyceollin I to the natural (−)-glyceollin I enantiomer, which was compared to those of the racemate and of the unnatural (+) enantiomer (Payton-Stewart et al, 2010).…”
Section: Natural Xenoestrogensmentioning
confidence: 67%
“…In particular, pterocarpans such as coumesterol, glyceofuran, glyceollin III suppressed the oxidation of low-density lipoprotein (LDL) [20], and have been reported to have cancer prevention and anti-inflammatory effects [21,22,23]. In addition, glyceollins (I–III), prenylated pterocarpan have known antiestrogenic effects in vivo [24,25]. In a previous study, soy leaf exhibited non-HDL-cholesterol lowering effects in hamsters [26]—as well as ethyl acetate extracts of soybean leaves, including pterocarpan—ameliorated the insulin sensitivity and improved the plasma glucose levels in high-fat diet (HFD)-induced type 2 diabetic mice [27].…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies of glyceollins' biological effects indicated that they were estrogen receptor antagonists (6), exhibited anti-proliferative effects in estrogen-dependent breast cancer cells (7), and inhibited cell proliferation in mouse xenograft breast cancer models (8). More recently, glyceollins demonstrated improvement in glucose homeostasis in response to a glucose challenge in a prediabetic rat model of type 2 diabetes (9) and lowered cholesterol in a hamster model of human cholesterol metabolism (10).…”
Section: Introductionmentioning
confidence: 99%